A critical analysis of helminth immunotherapy in multiple sclerosis. (October 2020) - Charabati, Marc; Donkers, Sarah J; Kirkland, Megan C; Osborne, Lisa C
Helminthic worms are ancestral members of the intestinal ecosystem that have been largely eradicated from the general population in industrialized countries. Immunomodulatory mechanisms induced by some helminths mediate a "truce" between the mammalian host and the colonizing worm, thus allowing for long-term persistence in the absence of immune-mediated collateral tissue damage. This concept and the geographic discrepancy between global burdens of chronic inflammatory diseases and helminth infection have sparked interest in the potential of using helminthic worms as a therapeutic intervention to limit the progression of autoimmune diseases such as multiple sclerosis (MS). Here, we present and evaluate the evidence for this hypothesis in the pre-clinical animal model of MS, experimental autoimmune encephalitis, in helminth-infected MS patients and in clinical trials of administered helminth immunotherapy (HIT).